Administrative Reform and the Quest for Openness: A Popperian Review of Open Government. Issue 2 (February 2020) - Ingrams, Alex
Scholars and policymakers claim open government offers a panoply of good governance benefits, but it also risks political abuse as window dressing or a smokescreen. To address this risk, this article builds on the meaning of openness through an examination of closed and open society in Karl Popper's theory. Four historic trends in open government reform are analyzed. The findings suggest a need for new attention to Popperian notions of the social technologist's piecemeal change and mechanical engineering aimed at serious policy problems. Without appreciation of these open society linkages, open governments will continue to paradoxically co-exist alongside closed societies.